A case with neuromyelitis optica mimicking Susac’s syndrome - Uygunoğlu, Uğur; Birke, Gunnar; Uluduz, Derya; Saip, Sabahattin (Neurological sciences, 2013)
Neuromyelitis optica (NMO) has been regarded as a disease sparing brain and a negative brain MRI was considered to be one of the major supportive criteria for the diagnosis in extant reports [1]. A landmark advance in this regard was the identification of NMO IgG, facilitating appreciation of NMO brain lesions [2]. Susac’s syndrome (SS) is a rare microangiopathic disease involving cerebral, retinal and cochlear arterioles in which MRI is a most helpful tool for diagnosis [3]. We present a patient with NMO who had initial misdiagnosis of SS.
Published online: 4 October 2012
Gesehen am 21.02.2022